Applicability of Pasteur's Quadrant in research of stricto sensu courses: Nursing (Research, Society and Development, 2020)
This study aimed to reflect the use of the propositions of the work O Quadrrante de Pasteur and its applicability in research of stricto sensu courses in nursing. To this end, a reflective theoretical study of a descriptive and qualitative nature was carried out. The scientific literature was also used to support the discussion and critical analysis, including books and scientific articles, obtained in online databases and in the sectoral library of a university institution, looking for references that adhered to the theme. In view of the analysis, it was possible to reflect that the considerations inherent to what Stokes calls Pasteur's Quadrant, underpin the theoretical reflection on the need to foster discussions about the most varied types of research in the stricto sensu modality in order to obtain the long-dreamed technological advance from research results in different academic and professional modalities. Given the above, it was possible to conclude that the research modalities in Pasteur's Quadrant are necessary for technological advances one at a time, with basic research being inspired by use as an alternative framing the current needs of society and academia.